2016
DOI: 10.37237/070306
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Attendance in a Self-Access Language Lounge

Abstract: Scheduled class time for students in tertiary language classes is limited, and is likely insufficient in itself to enable students to attain second language mastery (Nunan, 1989). Provision of language practice can be expanded outside regular class time through various means, including self-access centers. However, without effective marketing and management, and effective teaching staff, such facilities risk low participation rates. The current paper discusses the provision of an English language conversation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Time allotment for English classes is not enough for students to attain proficiency in the language. Nunan, 1989, as cited in Bibby, Jolley, and Sihiobara [14], reiterated that "scheduled class time for students in tertiary language classes is limited, and is likely insufficient in itself to enable students to attain language mastery." This is one of the reasons the respondent-university established its own English lounge.…”
Section: B Conversation Loungesmentioning
confidence: 99%
“…Time allotment for English classes is not enough for students to attain proficiency in the language. Nunan, 1989, as cited in Bibby, Jolley, and Sihiobara [14], reiterated that "scheduled class time for students in tertiary language classes is limited, and is likely insufficient in itself to enable students to attain language mastery." This is one of the reasons the respondent-university established its own English lounge.…”
Section: B Conversation Loungesmentioning
confidence: 99%
“…Finally, research into COPs often foregrounds issues of identity, interdependence, accountability, and self-sustainability among community members (Wenger, 1998;Wenger, McDermott, & Snyder, 2002). The authors found that this was reflected in a growing focus on community building within the field of self-access learning, where the COP framework had been adopted in a number of studies (Bibby, Jolley, & Shiobara, 2016;Gillies, 2010;Murray & Fujishima, 2013), thus justifying its use in the analysis of the English Lounge.…”
Section: Communities Of Practicementioning
confidence: 99%
“…Depending on the institution, students' use of the lounge might be optional (e.g. Bibby et al, 2016), incentivized (e.g. Taylor et at., 2012), or scaffolded (e.g.…”
Section: Conversation Loungesmentioning
confidence: 99%
“…This means that we need to consider learners' social needs. Providing access to the community via social events encourages initial participation (Bibby et al, 2016) which often leads to deeper engagement with the community that is needed for language learning.…”
Section: Social Interactionmentioning
confidence: 99%